Analisis Current Ratio, Debt To Equity Ratio, dan Total Asset Turnover Terhadap Profitabilitas pada Subsektor Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Rossy Rosmalia Sutarya; Nor Norisanti; Erry Sunarya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In Indonesia’s economic growth, the telecommunications industry has become a growing company along with the rapid development of technology, information and communication. With this growth, it is necessary to compare various financial statements, especially the balance sheet and income statement to determine the profitability of the company’s. The result of this study indicate that Return On Asset in telecommunications subsector listed on the Indonesia Stock Exchange for the 2020-2022 period has decreased drastically. The research method used is descriptive and assiciative with quantitative approach. The population used in the study is the financial statements of the telecommunications subsector listed on the Indonesia Stock Exchange period 2020-2022. The research object are Current Ratio (X1), Debt to Equity Ratio (X2), Total Asset Turnover (X3) and Profitability (Y). The data analysis techniques used intihs study are descriptive statistics and multiple linear regression. The result showed that partially (t test) Current Ratio has no significant effect on profitability, Debt to Equity Ratio has no significant effect on profitability, and Total Asset Turnover has a negative and significant effect on profitability. However, simultaneously (f test) Current Ratio, Debt to Equity Ratio, and Total Asset Turnover have a significant influence on the profitability of the telecommunications subsector listed on Stock Exchange for the period 2020-2022.